RELATIONSHIP BETWEEN SELF ESTEEM AND ADVERSITY QUOTIENT WITH SELF REGULATED LEARNING FOR STUDENTS MAJORING IN GEOGRAPHY EDUCATION FKIP USK - Sari, Annisa Sucia; Abdi, Abdul Wahab; Purnomowati, Dyah Rahmani (Jurnal Ilmiah Mahasiswa Pendidikan Geografi, 2024)
Independence is very important in one's life because with independence students are better able to overcome the difficulties that occur. One example of independence is independence in learning. Self esteem and adversity quotient are the most powerful internal factors influencing a student's independent learning. This study aims to determine the relationship between self-esteem and adversity quotient with the learning independence of students of the USK FKIP Geography Education Department. This study uses a quantitative approach and a type of correlational research. The population in this study were 382 active students of the Department of Geography Education, FKIP USK. The samples taken were 79 students. The sampling technique is proportional random sampling. The data collection technique used in this study was a questionnaire. Data analysis technique uses multiple correlation. Based on the results of statistical analysis it is known that the relationship between self esteem and adversity quotient with learning independence is obtained by the multiple regression equation Y = 55,76 + 0,12X1 + 0,10X2 which means that the two independent variables have a positive influence on the dependent variable. The correlation coefficient of self esteem and adversity quotient with learning independence is 0,17 very low, the correlation of self esteem with learning independence is 0,15 very low, the value of the correlation coefficient of adversity quotient with learning independence is 0,14 very low, the correlation of self esteem with adversity quotient of 0,30 is low, and the coefficient of determination (R2) = 2,9%. The results of the significance test showed Fcount (1,13) Ftable (3,12) at a significance level of 5% so that accepting H0 means that there is no significant relationship between self esteem and adversity quotient with the learning independence of students of the Department of Geography Education FKIP USK.Keywords: Relationship, Self Esteem, Adversity Quotient, Independent Learning